Strategy for Art and Cultural Preservation at Balinese Hindus in Praya City, Central Lombok Regency - Widana, I Nyoman Murba (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2017)
This study aimed to review the strategy of cultural preservation among Balinese Hindus in Kota Praya, Central Lombok Regency. This study uses qualitative descriptively in order to find answers the research problems. The focus of this research is the action taken by the people of Bali in Central Lombok in order to preserve the cultural heritage of their ancestors...